2018
DOI: 10.1016/j.virusres.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing elucidates cacao badnavirus diversity and reveals the existence of more than ten viral species

Abstract: Cacao swollen shoot virus is a member of the family Caulimoviridae, genus Badnavirus and is naturally transmitted to Theobroma cacao (L.) by several mealybug species. CSSV populations in West African countries are highly variable and genetically structured into several different groups based on the diversity in the first part of ORF3 which encodes the movement protein. To unravel the extent of isolate diversity and address the problems of low titer and mixed viral sequences in samples, we used Illumina MiSeq a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 26 publications
3
54
0
Order By: Relevance
“…These large-scale studies assess the spatial and temporal distribution of plant virus populations within specific ecosystems, helping deciphering key components of viral evolution and disease emergence that shape wild and cultivated habitats in important agro-ecological interfaces (Alexander et al, 2014). In addition, some of the HTS-based approaches allow for full genome assembly, facilitating genome-wide studies (De Souza et al, 2017; Hily et al, 2018a; Muller et al, 2018), which were rarely feasible during the Sanger-sequencing era. Finally, RNA seq-based techniques can provide comprehensive transcriptomic analyses enabling the evaluation of gene expression between different phenological stages or varieties (Zenoni et al, 2010; Massonnet et al, 2017), the monitoring responses to environmental constraints (such as drought, temperature) (Haider et al, 2017; Londo et al, 2018) or the study of plant responses to specific infectious agent (Gambino et al, 2012; Blanco-Ulate et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These large-scale studies assess the spatial and temporal distribution of plant virus populations within specific ecosystems, helping deciphering key components of viral evolution and disease emergence that shape wild and cultivated habitats in important agro-ecological interfaces (Alexander et al, 2014). In addition, some of the HTS-based approaches allow for full genome assembly, facilitating genome-wide studies (De Souza et al, 2017; Hily et al, 2018a; Muller et al, 2018), which were rarely feasible during the Sanger-sequencing era. Finally, RNA seq-based techniques can provide comprehensive transcriptomic analyses enabling the evaluation of gene expression between different phenological stages or varieties (Zenoni et al, 2010; Massonnet et al, 2017), the monitoring responses to environmental constraints (such as drought, temperature) (Haider et al, 2017; Londo et al, 2018) or the study of plant responses to specific infectious agent (Gambino et al, 2012; Blanco-Ulate et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A pipeline similar to that described in Muller et al . () was used for the processing of NGS data and characterization of badnavirus diversity. Raw reads were trimmed to obtain optimum quality using the dynamic trim function of S olexa QA ++ v. 3.1.3 (Cox et al .…”
Section: Methodsmentioning
confidence: 99%
“…Undigested RCA products of 10 Papua New Guinea (PNG) samples Quality of the raw reads was assessed with FastQC v. 0.10.1 (Babraham Bioinformatics). A pipeline similar to that described in Muller et al (2018) was used for the processing of NGS data and characterization of badnavirus diversity. Raw reads were trimmed to obtain optimum quality using the dynamic trim function of…”
Section: Next-generation Sequencing and Genome Assemblymentioning
confidence: 99%
“…Recent molecular studies with the use of advance sequencing methods such Next generation tools have provided the opportunity to further classify CSSV isolates across the West African sub-region into new groups based on their molecular information at the DNA level. Some of these studies have identified wide variability in the strains of the virus and virulence of the disease in new infections especially in the Western region of Ghana [3,19,20] CSSV is semi-persistently transmitted by several species of mealybugs (Pseudococcidae, Homoptera) on cocoa [21,22]. The vectors feed on all parts of the cocoa tree including flowers, cherelles, pods and leaves.…”
Section: Cssvd Isolates and Strainsmentioning
confidence: 99%
“…The cacao swollen shoot virus disease (CSSVD) which is considered the most economically important cocoa virus disease could account for 15-50% yield loss if the severe strains are involved in infections [2,3]. Since the discovery of this important disease in Ghana, it has been managed through the "cutting out and replanting system" with the aim of removing sources of inoculum from affected cocoa plantations and replanting with tolerant cocoa hybrids [3][4][5]. Nonetheless, reports from many reassessments and disease surveys indicate that the prevalence of the disease is still high with varying virulence across the cocoa regions.…”
Section: Introductionmentioning
confidence: 99%